Quantitative histological study of enteropathy associated with HIV infection. Issue 3 (March 1990) - Cummins, A G; LaBrooy, J T; Stanley, D P; Rowland, R; Shearman, D J
Abstract : A quantitative histological study was performed on small intestinal biopsies from eight ambulatory patients with HIV infection (AIDS/AIDS-related complex, ARC) and compared with those from 16 normal subjects. Enteropathy was assessed by measurement of villus area, crypt length and mitotic count, as well as duodenal counts of intraepithelial lymphocytes, mucosal mast cells and goblet cells. Enteropathy in subjects with AIDS/ARC was shown by reduced mean villus area of 0.363 (SD 0.081) compared with 0.500 (SD 0.064) mm2 in control subjects (p less than 0.0001), while intestinal crypts were of similar length with 239 (SD 36) compared with 225 (SD 28 microns, but mitotic count was increased to 3.8 (SD 1.2) compared with 2.4 (SD 0.8) (p = 0.01) in the same control subjects. These results indicate villous atrophy with impaired crypt hyperplasia. Duodenal cell counts showed similar numbers of mucosal mast cells, intraepithelial lymphocytes and goblet cells in AIDS/ARC patients and fifteen control subjects.